PROFESSIONAL LEARNING COMMUNITY TO PROMOTE ANALYTICAL READING AT PADENGVITTAYA SCHOOL THE SECONDARY EDUCATION SERVICE AREA OFFICE PHETCHABURI - Chusri, Pailin; Jumpaluang, Monta (Journal of MCU Phetchaburi Review, 2023)
In solving the learning management problems in schools, there is an administrative principle able to be used for solving the problems by using the process of creating professional learning community (PLC). The researcher was, therefore, interested in doing the study on creation of PLC to promote analytical reading of Padengwittaya School under the Secondary Educational Service Area Office Phetchaburi with the objectives to: 1) create PLC in the aspect of analytical reading of Padengwittaya School, and 2) develop analytical reading skill of students at Padengwittaya School under the Secondary Educational Service Area Office Phetchaburi. The study target group consisted of 6 teachers and the students in Mathayomsuksa 1-3 (Grade 7-9) at Padengwittaya School. The steps of study were: 1) planning, 2) implementation, and 3) reflection. The research tools were a questionnaire, a test paper, a recording form, an assessment form, a semi-structured interview form, a learning management plan, and focus group discussion. The data were analyzed by using percentage, mean, standard deviation, and t-test. The research results were as follows: The creation of PLC in analytical reading at Padengwittaya School consisted of three stages: 1] Planning stage: organizing according to three components of creating PLC as follows: 1) mutual support and leadership aspect by teachers jointly analyzing, synthesizing concepts and theories of creating PLC, 2) value and shared vision building aspect by teachers attending the meeting to assess and prioritize problems and needs on analytical reading, and 3) favorable condition arrangement aspect by setting up 3 professional learning teams (PLT), 2 people each (buddy) at PADENG PLC Zone, 2] Implementation stage: following the process of creating PLC in the aspects of collaborative learning and application of knowledge by allowing PLT members to participate in observation of teaching and learning, consisting of 1) model teachers, the main teachers teaching Thai language courses, 2) co-learning teachers, 3) learning area leaders, 4) administrators, and 5) specialists, and the final stage, 3] Reflection stage: sharing experiences in solving learning management problems in classroom. The results of developing analytical reading skill of students in Mathayomsuksa 1-3 at Pa Deng Wittaya School under Secondary Educational Service Area Office Phetchaburi using a test consisting of comparative skill, classification skill, sorting skill, link skill, and proof skill, revealed that the average score in all aspects and classified by aspects were different with statistical significance at the .01 level.